2015
DOI: 10.1038/ncomms9759
|View full text |Cite
|
Sign up to set email alerts
|

Torso-like mediates extracellular accumulation of Furin-cleaved Trunk to pattern the Drosophila embryo termini

Abstract: Patterning of the Drosophila embryonic termini is achieved by localized activation of the Torso receptor by the growth factor Trunk. Governing this event is the perforin-like protein Torso-like, which is localized to the extracellular space at the embryo poles and has long been proposed to control localized proteolytic activation of Trunk. However, a protease involved in terminal patterning remains to be identified, and the role of Torso-like remains unknown. Here we find that Trunk is cleaved intracellularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…We chose to manipulate InR activity specifically in the PG because it is well established as the key tissue involved in the InR-mediated regulation of ecdysone production (Mirth et al 2005), and because we know that tsl is expressed there (Grillo et al 2012 In the early embryo our work has led us to hypothesise that Tsl is required for the secretion of the Tor ligand, Trunk (Henstridge et al 2014;Johnson et al 2015). We therefore reasoned that it might regulate secretion of the dILPs, the ligands for InR.…”
Section: Resultsmentioning
confidence: 99%
“…We chose to manipulate InR activity specifically in the PG because it is well established as the key tissue involved in the InR-mediated regulation of ecdysone production (Mirth et al 2005), and because we know that tsl is expressed there (Grillo et al 2012 In the early embryo our work has led us to hypothesise that Tsl is required for the secretion of the Tor ligand, Trunk (Henstridge et al 2014;Johnson et al 2015). We therefore reasoned that it might regulate secretion of the dILPs, the ligands for InR.…”
Section: Resultsmentioning
confidence: 99%
“…For example, MACPF proteins facilitate the invasion and/or proliferation of intracellular pathogens, such as Toxoplasma gondii, Plasmodium falciparum and Chlamydia, all of which must traverse cellular membrane barriers during their life cycles (Blackman and Carruthers, 2013;Taylor andNelson, 2014, Wade and. In addition, several MACPF proteins have roles in embryonic development (Estévez-Calvar et al, 2011;Johnson et al, 2015) and in neural migration (Kawano et al, 2004;Giousoh et al, 2015).…”
Section: The Macpf-cdc Superfamilymentioning
confidence: 99%
“…Previous models for Torso activation in the embryo have suggested that Tsl exerts its effects through Trk, either by promoting its processing (Casali and Casanova, 2001) or by facilitating its secretion at the poles (Johnson et al, 2015). Although our experiments in S2R+ cells do not necessarily reflect the situation in the embryo, our results suggest that Tsl is likely to play another role, possibly in addition to effects on Trk processing/secretion.…”
Section: Discussionmentioning
confidence: 53%
“…This led them to propose that Tsl controls Torso activation by mediating the cleavage of Trk into an active form only at the poles of the embryo. Henstridge et al (2014) demonstrated that Trk does undergo processing in embryos, but at least some of the cleavage events are mediated by Furin proprotein convertases (Johnson et al, 2015) and are not Tsl dependent. Johnson et al (2015) reported that secretion from the embryo of a fluorescent fusion protein containing N-terminal Trk sequences is enhanced by Tsl activity, leading them to propose that the role of Tsl is to promote secretion of Trk into the perivitelline fluid specifically at the two ends of the embryo.…”
Section: Introductionmentioning
confidence: 99%